GEOLOGY OF PLANTUNGAN AREA AND SURROUNDINGS, BLORA AND REMBANG DISTRICT, CENTRAL JAVA PROVINCE - Halim, Jonatan
The plantungan area, Blora regency, and Rembang, are areas located in the East Java Basin known for its gas and natural oil commodities. Geological mapping is necessary to explain geological events in this area. So the research was conducted with the aim to study the geological history in the area of Plantungan and its surroundings, through geomorphology, stratigraphy and geological structure. The research area is located at 111° 26' 05,62" 111° 30' 08,66" East Longintude dan 6° 51' 00,37" 6° 55' 56,47" South Latitude. The methods used in this research are laboratory method and field method. Laboratory methods undertaken prior to the field work are geomorphological analysis through SRTM imagery, and topography; and regional geological literature review of the research area. Then the research is performed by collecting primary data with field observation and rock sampling in the research area. After that the research is done in the laboratory by doing stratigraphy, structural geology, micropaleontology, and petrography analysis. So geomorphologically, the research area can be divided into Unit of Folded Plains, Unit of the Folded Hills, and Unit of Karst Hills. The research area stratigraphy units are divided by lithostratigraphic classification. So, it is divided into Packestone-Sandstone Unit, Sandstone Unit, Packstone Unit 1, Packestone-Marl Unit, Packestone Unit 2, Marl Unit, Boundstone Unit, and Alluvial Unit. It is deposited from Middle Miocene to Holocene. Based on stratigraphic profile and biostratigraphic analysis, sea level on research area was found shallowing from lower Middle Miocene to middle Middle Miocene, and deepening from middle Middle Miocene to lower Early Pliocene.Between Early Pliocene-Pleistocene there was a deformation that expose research area to terresterial. Then Im Pleistocene research area was shallow marine environment, and expose again in Holocene. in The structural geology that can be identified in the research area are folding, and a pair of strike-slip fault with the direction of maximum principle stress Southwest-Northeast, which was formed at the age of Pliocene to Plistocene.